Analisis Penerapan Teknik Lipat Origami Folded Plate dan Yoshimura pada Purwarupa Kap Lampu Berbahan Kulit - Fahmi, Amelia Isti (Telkom University, 2024)
Origami is a form of paper craft with techniques that can applied to other materials, one of which is leather. This study attempts to identify a number of physical characteristics of leather materials in the author's previous work, namely decorative lamp shades in three lamp prototypes. Specifically, the author examines the physical characteristics that arise when leather materials are formed using the folded plate and Yoshimura origami techniques. The application of origami technique to leather has limitations due to conventional leather’s inherent elasticity and material thickness which are unable to produce sharp crease angles. During the making of the prototype, it was found that the fold crease can be made more prominent by cutting lines to the leather surface and applying pressure parallel to the direction of the lines. Cut line on the outside surface of 1,5 mm thick vegetable tanned leather pattern produce the sharpest crease fold that is visually closest to the paper folds. However, scratches on the outside produce visible cuts that are less aesthetic, therefore scratches on the inside surface of the leather are used as an alternative that produces the closest shard fold crease. In addition to emphasizing the fold line, the process of soaking in water can make the folds on the leather last longer and allow for more extreme shapes.